Evaluasi Penugasan Clinical Reasoning dan Refleksi Mahasiswa di SKills Lab FK UGM - Widyandana Widyandana (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2014)
Background: Teaching clinical reasoning and reflection skills in skills laboratory are usually neglected, therefore Skills Lab of FM UGM initiate to teach those skills for undergraduate students. This study aimed to evaluate student’s assignment of clinical reasoning and reflection skills and explore how to improve it.Method: An experimental study by giving student assignments to make an essay about particular disease based on SKDI level 4 that written on a medical record and reflection form format. All 4th-year medical students of FM GMU (n=186) and skills lab instructors (n=5) were involved. Assignments were assessed (by the instructors) using instrument by Driessen (2008), and analyzed by correlating those scores with students’ OSCE score and GPA using Pearson Correlation test. Qualitative data collected by deep interview with assessors and analyzed using Inductive Content Analysis by 2 coders.Results: There were no significant correlation between assignment score with OSCE score and GPA. However, there were significant correlations (p<0.05) between score of clinical reasoning with reflection skills, and OSCE score with GPA. Assessors conclude that assignment has been good enough to stimulate clinical reasoning and reflection skills, but still had weaknesses e.g. incompatibility of assignment’s format to assessment’s checklist, unclear instructions, and no assignment’s sample that made students submitted in various format.Conclusion: The assignment has been successfully conducted in Skills Lab FM UGM, however it needs some improvement, such as giving detail instructions, examples, and matching it with assessment instrument.